Peran media sosial dalam membangun citra bisnis di era digital - Agusty, rizal ubaidilbar; Sri Rahayu, Yayuk (Maliki Interdisciplinary Journal, 2025)
Advancements in digital technology have significantly reshaped how businesses engage with consumers and establish their brand image. Social media, originally created for social interaction, has evolved into a highly strategic platform for corporate communication and reputation management. This article explores how social media goes beyond being a promotional channel and functions as a powerful tool for shaping public perception through consistent, value-based engagement. Studies suggest that companies that actively manage their social media presence and maintain interactive relationships with their audience are more likely to gain trust and customer loyalty. Furthermore, social media enables businesses to openly share their values, vision, and corporate culture, which contributes to a stronger and more credible brand identity. This article also outlines effective digital communication strategies for branding, including structured content delivery, engaging visuals, and audience participation. Thus, social media is an essential asset in building a strong and lasting business identity in today’s digital marketplace